The Stem Infusate and Ethanol Extract of Physalis angulata Inhibitory Activities against a-Glucosidase and Xanthine Oxidase - Anthony Tjajaindra; Anna Karmila Sari; Adelina Simamora; Kris Herawan Timotius (Molecular and Cellular Biomedical Sciences, 2021)
Background: Infusate of the whole plant of Physalis angulata is used traditionally for the remedy of various diseases including diabetes and gout. This study focused on the stem of P. angulata. The objectives of this study were to investigate the potential of the stem infusate (INPA) and ethanol extract (EEPA) of P. angulata as inhibitors of α-glucosidase and xanthine oxidase.Materials and Methods: INPA and EEPA were determined for their α-glucosidase and xanthine oxidase inhibition activities in vitro, whereas antioxidant activity was determined by 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) assay. Reference inhibitors were used for comparison. The total phenolic compounds were also estimated.Results: EEPA had more concentrated phenolic than INPA which were 7.96 and 0.08 mgGAE/g dried biomass, respectively. INPA and EEPA inhibited α-glucosidase considerably, with IC50 of 149.11 and 409.86 µg/mL, respectively (acarbose was 130.66 µg/mL). However, they inhibited xanthine oxidase weakly, with IC50 of 0.546 and 2.643 mg/mL, respectively, compared with allopurinol 0.005 mg/mL. EEPA scavenged DPPH radicals very weakly (16.04 mg/mL) compared to BHT (0.021 mg/mL), whereas no activity was observed for INPA.Conclusion: The stem infusate and ethanol extract of P. angulata are able to inhibit the activity of α-glucosidase, thus can be further explored for sources of bioactive compounds with α-glucosidase inhibition activity.Keywords: α-glucosidase, infusate, ethanol extract, Physalis angulata, stem, xanthine oxidase